Telehealth Care Through Internet Hospitals in China: Qualitative Interview Study of Physicians' Views on Access, Expectations, and Communication - Yuqiong Zhong; Jessica Hahne; Xiaomin Wang; Xuxi Wang; Ying Wu; Xin Zhang; Xing Liu (JMIR Publications, 2024)
BackgroundInternet hospitals in China are an emerging medical service model similar to other telehealth models used worldwide. Internet hospitals are currently in a stage of rapid development, giving rise to a series of new opportunities and challenges for patient care. Little research has examined the views of chronic disease physicians regarding internet hospitals in China. ObjectiveWe aimed to explore the experience and views of chronic disease physicians at 3 tertiary hospitals in Changsha, China, regarding opportunities and challenges in internet hospital care. MethodsWe conducted semistructured qualitative interviews with physicians (n=26) who had experience working in internet hospitals affiliated with chronic disease departments in 3 tertiary hospitals in Changsha, Hunan province, south central China. Interviews were transcribed verbatim and analyzed by content analysis using NVivo software (version 11; Lumivero). ResultsPhysicians emphasized that internet hospitals expand opportunities to conduct follow-up care and health education for patients with chronic illnesses. However, physicians described disparities in access for particular groups of patients, such as patients who are older, patients with lower education levels, patients with limited internet or technology access, and rural patients. Physicians also perceived a gap between patients' expectations and the reality of limitations regarding both physicians' availability and the scope of services offered by internet hospitals, which raised challenges for doctor-patient boundaries and trust. Physicians noted challenges in doctor-patient communication related to comprehension and informed consent in internet hospital care. ConclusionsThis study explored the experience and views of physicians in 3 tertiary hospitals in Changsha, China, regarding access to care, patients' expectations versus the reality of services, and doctor-patient communication in internet hospital care. Findings from this study highlight the need for physician training in telehealth communication skills, legislation regulating informed consent in telehealth care, public education clarifying the scope of internet hospital services, and design of internet hospitals that is informed by the needs of patient groups with barriers to access, such as older adults.